GAMBARAN PENGETAHUAN, SIKAP, DAN TINDAKAN PENGOBATAN SENDIRI PADA PASIEN DI PUSKESMAS SUKARAMAI MEDAN - NELLI MURLINA; RIJENA KARINA ABIGAEL BANGUN (LP2MTBM MAKARIOZ, 2022)
Self-medication or self-sufficiency is the selection and use of drugs by individuals to treat a self-recognized disease orsymptom. Basic Health Research 2013 in Indonesia reported a total of 103,860 (35%) of the 294,959 households stored thedrug for self-treatment. Self-medication can be a source of medication error due to limited public knowledge. This study aimsto find out the picture of self-medication in patients at Sukaramai Medan health center. Descriptive research with a